Functional outcome of arthroscopic meniscal repair in meniscal tears: a prospective study in tertiary care hospital in North India - Singh, Simran Preet; Singh, Manish; Singh, Pankaj Vir; Singh, Sumitpal; Arif, Mudasir (International Journal of Research in Orthopaedics, 2021)
Background: A Meniscal injury can result in intra articular damage and which can eventually result in osteoarthritis if not treated on time and the objective should be to save the meniscus wherever possible. This study was done to analyse the functional outcome of arthroscopic meniscal repair done in different types of Meniscal tears. Methods: The study was conducted on a group of 28 patients with meniscal injury admitted in government medical college Jammu from November 2018 to October 2020. All the tears were located in the red-red and red-white zones. The functional outcome was assessed on the basis of Lysholm Tegner scoring. A standard rehabilitation protocol was followed post repair. Results: Twenty-eight patients were included in the study. Male patients outnumbered the females and the incidence of injury was more on the right side. Sports injuries were the most common mode of injury, followed by road traffic accidents and falls. Bucket handle tears were most commonly seen in the group of patients. ACL injury was the major associated injury to be noted. The functional outcome between pre and post operation was statistically significant (p<0.05). In one of the patient failures was seen. Two patients were lost to follow up and were not included in the study. Conclusions: Arthroscopic meniscal repair is a has a very good functional outcome according to our study and should be preferred over meniscectomy (subtotal or total), as meniscus being a very important shock absorber present between the knee joint can lead to delay in osteoarthritis of knee joint. Therefore, our priority should be to save the meniscus and restore the normal anatomy of the knee joint for its biomechanical stability and normal function.